Examining Gender Responsiveness of the Philippine Basic Education Reform: An Analysis of the K-12 Araling Panlipunan or Social Studies Curriculum - Tantengco, Nerissa S; Maramag, Rodolfo L (MIMBAR PENDIDIKAN, 2016)
ABSTRACT: This study provides an in-depth analysis on how gender issues, concepts, and principles were integrated in the recent K-12 Araling Panlipunan or Social Studies curriculum provided by the Department of Education in the Philippines. The study employed descriptive analysis of the K-12 Araling Panlipunan or Social Studies curriculum content covering grades one to ten. Findings have shown that promoting gender-fair education is a commitment of different educational institutions in the country, both private and public. Social Studies are the curriculum vehicle of the K-12 Basic Education Reform to promote active citizenship and social transformation. The new Social Studies Curriculum of the K-12 Basic Education Reform tries to respond in integrating gender-principles and concepts in the teaching-learning process by providing curriculum content that recognizes womenâ€™s significance in the society as product of historical and cultural processes. The school serves as an agent of social transformation by creating curricula that provide learning experiences that will harness social criticism and action towards contemporary issues in the country. KEY WORD: Development, gender-fair education, Social Studies curriculum, and transformative education.Â ABSTRAKSI: â€œMengkaji Ketanggapan Gender dalam Reformasi Pendidikan Dasar di Filipina: Sebuah Analisis terhadap K-12 Araling Panlipunan atau Kurikulum Ilmu Pengetahuan Sosialâ€. Penelitian ini menganalisis secara mendalam isu-isu gender, konsep, dan prinsip-prinsip yang terintegrasi dalam kurikulum terbaru K-12 Araling Panlipunan atau Kurikulum Ilmu Pengetahuan Sosial, yang diberikan oleh Kementerian Pendidikan di Filipina. Penelitian ini menggunakan analisis deskriptif terhadap isi K-12 Araling Panlipunan atau Kurikulum Ilmu Pengetahuan Sosial yang meliputi kelas satu sampai sepuluh. Temuan menunjukkan bahwa mempromosikan pendidikan gender yang adil merupakan komitmen dari lembaga pendidikan yang beragam di negara ini, baik swasta dan negeri. Ilmu Pengetahuan Sosial adalah wahana bagi kurikulum Reformasi Pendidikan Dasar K-12 untuk mempromosikan warganegara yang aktif dan transformasi sosial. Kurikulum baru Ilmu Pengetahuan Sosial dalam Reformasi Pendidikan Dasar K-12 mencoba merespons persyaratan untuk mengintegrasikan konsep dan prinsip gender dalam proses belajar-mengajar dengan menyediakan materi kurikulum yang mengakui pentingnya perempuan dalam masyarakat sebagai produk dari proses sejarah dan budaya. Sekolah berfungsi sebagai agen transformasi sosial dengan menciptakan kurikulum dan memberikan pengalaman belajar yang akan memanfaatkan kritik sosial dan tindakan nyata terhadap isu-isu kontemporer di negara ini. KATA KUNCI: Pembangunan, pendidikan adil bagi gender, kurikulum Ilmu Pengetahuan Sosial, dan pendidikan transformatif.About the Authors: Nerissa S. Tantengco, Ph.D. is a Professor in Southeast Asian Studies at the (Philippine Normal University). Rodolfo L. Maramag, M.A. is a Lecturer in Philippine Studies at the PNU in Manila, the Philippines. Corresponding authors is: tantengco.ns@pnu.edu.phHow to cite this article? Tantengco, Nerissa S. Rodolfo L. Maramag. (2016). â€œExamining Gender Responsiveness of the Philippine Basic Education Reform: An Analysis of the K-12 Araling Panlipunan or Social Studies Curriculumâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.1(1) Maret, pp.37-54. Bandung, Indonesia: UPI Press. Chronicle of the article: Accepted (December 15, 2015); Revised (January 15, 2016); and Published (March 11, 2016).